2017
DOI: 10.1093/qjmed/hcx200
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin D status and parameters of calcium metabolism in patients with primary hyperparathyroidism

Abstract: Vitamin D repletion in PHP seems safe. Considering the documented adverse influence of vitamin D deficiency in PHP, particularly on skeletal manifestations and on the postoperative course, vitamin D repletion is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…(1,2,6,(15)(16)(17)20,21) In contrast, an isolated study has documented a lack of exaggerated rise in already existent hypercalcemia upon vitamin D supplementation. (12) However, in this study, 25OHD remained subnormal probably because of inadequate supplementation. The rise in serum calcium in our study, and in others, may be attributed to a further exaggerated rise in 1,25 (OH)D and a lack of suppression or a paradoxical rise of elevated PTH.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…(1,2,6,(15)(16)(17)20,21) In contrast, an isolated study has documented a lack of exaggerated rise in already existent hypercalcemia upon vitamin D supplementation. (12) However, in this study, 25OHD remained subnormal probably because of inadequate supplementation. The rise in serum calcium in our study, and in others, may be attributed to a further exaggerated rise in 1,25 (OH)D and a lack of suppression or a paradoxical rise of elevated PTH.…”
Section: Discussioncontrasting
confidence: 59%
“…The presence of low serum 25OHD in subjects with PHP is wellestablished. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) However, concurrently elevated serum 1,25 (OH)D concentrations in subjects with PHP have rarely been reported in the past 30 years. (15)(16)(17) This study also found normalization of mean concentrations of serum calcium, 25OHD, and 1,25(OH)D following a decline in circulating serum PTH levels after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations